Genistein and enterolactone in relation to Ki‐67 expression and HER2 status in postmenopausal breast cancer patients. Issue 11 (1st September 2017) - Jaskulski, Stefanie; Jung, Audrey Y.; Rudolph, Anja; Johnson, Theron; Thöne, Kathrin; Herpel, Esther; Sinn, Peter; Chang‐Claude, Jenny
Abstract : Scope: Phytoestrogens (PE) may improve breast cancer prognosis by modifying tumor prognostic markers, such as cell proliferation marker Ki‐67 and human epidermal growth factor receptor 2 (HER2). Epidemiological evidence linking lignans and isoflavones to Ki‐67 and HER2 is limited. We examined associations between the major metabolites of lignans and isoflavones – enterolactone (ENL) and genistein (GEN) – respectively, and Ki‐67 expression and HER2 in tumor tissue of breast cancer patients. Methods and results: Data from 1060 invasive breast cancer patients from the population‐based MARIE study were used. Multivariate‐adjusted linear (Ki‐67 log‐transformed) and quantile regression, and logistic regression analyses (HER2, Ki‐67 dichotomized) were performed to calculate β estimates and ORs, respectively. Median post‐diagnostic ENL and GEN concentrations were 19.5 and 4.8 nmol/L, respectively. Median Ki‐67 was 12.0%, and 21.2% of the tumors were HER2+. After adjustment, there was an inverse association between GEN and Ki‐67 at high expression levels (OR for Ki‐67 ≥20% versus <20% of 0.93 (95%CI [0.87;0.99]) per 10 nmol/L GEN increment). Conclusion: Our findings indicate an inverse association between GEN and Ki‐67 at high levels of Ki‐67 expression. Additional investigations are recommended to confirm our findings and to further elucidate mechanisms linking PE metabolites to breast cancer survival. Abstract : A high dietary intake of phytoestrogens (such as oilseeds, whole grains, and soy products) may improve survival after breast cancer diagnosis by modifying tumor markers that are known to be predictors of survival. We have found that when one of these tumor markers indicative of cell proliferation is very highly expressed in postmenopausal breast cancer patients, higher soy intake, as assessed in blood, is linked to a decreased expression of this tumor marker.